Penerapan Adat Waja (Denda) dalam Praktik Perkawinan Masyarakat Langa Kecamatan Bajawa, Kabupaten Ngada - Falentina Tekhu Soa; Yossie Maria Y. Jacob; Petornius Damat (Parlementer : Jurnal Studi Hukum dan Administrasi Publik, 2024)
For the Langa indigenous people, Waja is a process of recovery for mistakes because someone has violated a prohibition or certain customary law norms that apply in the Langa indigenous people. There are several marriage problems that occur in the Langa community that are not resolved with waja. The practice of waja serves to break the bond of engagement or marriage that has occurred between a man and a woman, the purpose is as a deterrent effect and also as a means of value education for the community so that marriages that violate customary norms can be eliminated or no longer repeated. This research is an empirical research, so the data source used is the primary data source, the primary data is obtained from the results of interviews. The data were analyzed in a descriptive-qualitative manner. The results of this study show that: (1) The function of waja customs in the marriage legal system of the Langa indigenous people is for the enforcement of customary norms and rules, the restoration of good name, efforts to break the bond of engagement or marriage between men and women and to realize justice and balance in community life, including in terms of marriage. (2) The process of applying waja customs in the practice of marriage of the Langa indigenous people is carried out in accordance with the marriage violations that have been carried out by both parties. The types of violations of waja customs are infidelity, relationships that are not approved by parents and abusive behavior of husbands towards wives.